2018
DOI: 10.2147/ott.s152611
|View full text |Cite
|
Sign up to set email alerts
|

miR-106b-5p promotes stem cell-like properties of hepatocellular carcinoma cells by targeting PTEN via PI3K/Akt pathway

Abstract: BackgroundThe miRNA miR-106b-5p has been previously reported to be increased in hepatocellular carcinoma (HCC) tissues compared to cirrhotic tissues. The purpose of this study was to detect its expression in HCC cell lines with distinct metastatic potentials and to explore the molecular mechanisms underlying HCC stemness and migration.MethodsmiR-106b-5p expression was studied in HCC tissues and cell lines. In vitro cancer stem cell (CSC)-like properties, cell migration and invasion were compared between HCC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 36 publications
(34 reference statements)
2
36
0
1
Order By: Relevance
“…Among these six miRNAs, miR-106b-5p has been reported to promote stemlike properties of HCC cells via targeting PTEN, consistent with our present study (Shi et al 2018). However, the expression level of miR-125b-5p increased in the serum of HBV-positive HCC patients compared with matched controls, which is contradictory to our findings (Giray et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Among these six miRNAs, miR-106b-5p has been reported to promote stemlike properties of HCC cells via targeting PTEN, consistent with our present study (Shi et al 2018). However, the expression level of miR-125b-5p increased in the serum of HBV-positive HCC patients compared with matched controls, which is contradictory to our findings (Giray et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, Pten deficiency promotes tumorigenicity, and approximately 50% of human cases of HCC lose PTEN expression . In fact, several micro‐RNAs can downregulate PTEN expression during progression of human HCC . Here, we demonstrated that hypercholesterolemia promotes tumor growth by accelerating angiogenesis in Pten Δhep mice.…”
Section: Introductionmentioning
confidence: 71%
“…19 In fact, several micro-RNAs can downregulate PTEN expression during progression of human HCC. 20,21 Here, we demonstrated that hypercholesterolemia promotes tumor growth by accelerating angiogenesis in Pten Δhep mice. Ezetimibe lowered cholesterol levels and inhibited angiogenesis, resulting in suppression of liver tumors in Pten Δhep mice on a high-fat (HF) diet.…”
mentioning
confidence: 88%
“…PTEN deletion results in the proliferation of a CD133+ population [71,98] . PI3K signaling promotes stem-like properties of HCC cells and it is implicated in HCC chemo-and radio-resistance as well as in epithelial-to-mesenchymal transition (EMT) and metastasis [99][100][101][102][103][104] . Notably, the co-activation of AKT and neuroblastoma rat sarcoma viral oncogene homolog (N-RAS) oncogenes leads to development of cHCC-CCA-like liver tumors, through the expansion of HPCs or malignant conversion of hepatocyte into progenitor-like cells [42] .…”
Section: Phosphatidyl Inositol 3-kinase/akt Signalingmentioning
confidence: 99%